Learning by Doing: The Benefits of Experiential Learning in Animals and the Law - Peter Sankoff (Legal Education Review)
The primary purpose of legal education is to teach students how to think like lawyers. However, given the opportunities and challenges involved, completing a Juris degree must also have an impact on the affective skills of students, but how so and to what extent? This longitudinal, mixed methods study was designed to answer this question by exploring changes in the affective skills of law students, utilizing the construct of emotional intelligence. Emotional intelligence (EI) is defined as the ability to identify, process, and manage emotions to effect positive behaviour. To assess the changes, quantitative data from emotional intelligence tests administered at the beginning of first year (pre) and the end of third year (post), as well as qualitative data from exit interviews were collected and analyzed. The quantitative findings from this study suggest attending law school enhances students’ EI, as the mean Total EI increased significantly along with nine of the fourteen mean subscale scores from the pre to the post assessment. The qualitative data supported these findings and provided some specific insights into how these changes manifested themselves during the students’ law education.